Genetic parameters and genomic regions associated with piglet response to vaccination for porcine reproductive and respiratory syndrome (PRRS) virus and co-infection with PRRS virus and porcine circovirus type 2b (PCV2b) - Dunkelberger, J. R.; Serao, N. V. L.; Kerrigan, M. A.; Lunney, J. K.; Rowland, Raymond R.; Dekkers, J. C. M. (My University, 2016)
Objectives of this research were to estimate genetic parameters and to identify genomic regions associated with PRRS viral load (VL), PCV2b VL, and average daily gain (ADG) in nursery pigs vaccinated or non-vaccinated for PRRS virus (PRRSV), followed by co-infection with PRRSV and PCV2b. Data used included 396 commercial crossbred pigs from two PRRS Host Genetics Consortium trials, all from the same genetic supplier. Pigs were sent to Kansas State University after weaning and randomly sorted into two rooms. All pigs in one room were vaccinated for PRRS, and 28 d later, pigs in both rooms were co-infected with PRRSV and PCV2b, followed for 42 d, and genotyped using the 80K BeadChip. PRRS VL after vaccination and post co-infection and PCV2b VL were calculated as area under the curve of serum viremia from ?28 to 0, 0 to 21, and 0 to 42 d post co-infection, respectively. Genetic parameters were estimated by fitting multivariate animal models in ASReml4 with litter and pen (trial) as additional random effects. Trait-specific fixed effects of trial and weight and age at vaccination were also fitted. Genome-wide association (GWA) studies were performed by fitting SNPs as fixed effects one at a time in bivariate animal models for the non-vaccinated (Non-Vx) and vaccinated (Vx) groups for each trait. Heritability estimates following vaccination were 0.31, 0.07, and 0.10 for ADG Non-Vx, ADG Vx, and PRRS Vx, respectively. During the co-infection period, heritability estimates were slightly higher at 0.53, 0.57, 0.56, 0.20, 0.18, and 0.15 for ADG Non-Vx, ADG Vx, PRRS Non-Vx, PRRS Vx, PCV2b Non-Vx, and PCV2b Vx, respectively. Standard errors ranged from 0.14 to 0.22. A strong, positive genetic correlation (0.95 ± 1.01) was observed for PRRS VL post-vaccination with PRRS VL Non-Vx. Unique genomic regions were identified between Vx and Non-Vx pigs for each trait, the most significant of which was identified for PCV2b VL and located near the major histocompatibility complex, an important region for response to infection. The chromosome 4 region, which has been associated with VL following PRRSV-only infection, was associated with PRRS VL Non-Vx but not PRRS Vx or PRRS VL post-vaccination. Together, these results suggest that selection for improved performance under co-infection of PRRS and PCV2b is possible. Additionally, identification of unique genomic regions between Vx and Non-Vx pigs may enable selection of pigs with better response to vaccination. This research was supported by USDA-NIFA grants 2012–38420–19286 and 2013–68004–20362.
Citation: Dunkelberger, J. R., Serao, N. V. L., Kerrigan, M. A., Lunney, J. K., Rowland, R. R. R., & Dekkers, J. C. M. (2016). Genetic parameters and genomic regions associated with piglet response to vaccination for porcine reproductive and respiratory syndrome (PRRS) virus and co-infection with PRRS virus and porcine circovirus type 2b (PCV2b). Journal of Animal Science, 94, 52-53. doi:10.2527/msasas2016-112
Keywords: Disease; Gwas; Swine; Agriculture